Comparison of peripheral blood cell characteristics in patients with vitamin B12 deficiency anemia with and without iron deficiency - Dung, Nguyen Ngoc; Thuy, Cao Thi; Khanh, Nguyen Ba (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2026)
Objective: To compare hematological characteristics in patients with vitamin B12 deficiency anemia with and without concomitant iron deficiency at the National Institute of Hematology and Blood Transfusion during the period 2024–2025. Methods: A retrospective cross-sectional study was conducted on 281 patients diagnosed with vitamin B12 deficiency anemia from January 2024 to December 2025. Patients were divided into two groups: vitamin B12 deficiency alone and vitamin B12 deficiency with concomitant iron deficiency. Hematological parameters were compared between the two groups. Results: The mean age was 51.4 ± 19.9 years, with a male-to-female ratio of 1:1.98. Mild and moderate anemia accounted for 93.6% of cases. Among 281 patients, 156 had isolated vitamin B12 deficiency, and 125 had concomitant iron deficiency. The isolated vitamin B12 deficiency group had significantly higher Hb, MCV, MCH, and MCHC compared to the combined deficiency group (90.5 g/L vs. 79.0 g/L; 104.6 fL vs. 69.1 fL; 34.8 pg vs. 20.8 pg; 332 g/L vs. 306 g/L, respectively; p < 0.001). Thrombocytopenia was more frequent in the isolated vitamin B12 deficiency group than in the combined deficiency group (39.1% vs. 5.6%; p < 0.05). The proportion of hypersegmented neutrophils was high in both groups (66.0% and 70.4%, respectively), with no statistically significant difference. Conclusion: Concomitant iron deficiency was associated with differences in red cell indices and some white blood cell and platelet features, potentially masking the typical hematological manifestations of vitamin B12 deficiency